128k views
3 votes
Which of the following equations could you solve by first adding six and then dividing by negative three? 3x - 6 = -9 6 - 3x = -9 -3x - 6 = -9 + 6 = -9

User Marko E
by
5.1k points

2 Answers

2 votes

Answer:

-3x - 6 = -9

Explanation:

I got it right on my test

hope it helps!!

User Guru Stron
by
5.6k points
3 votes

Answer:
-3x-6=-9

Explanation:

The proccedure shown in the problem is applied to solve for x and calculate its value.

One of the equations shown in the problem is:


-3x-6=-9

To solve for x you must_

- Add 6 to both sides of the equations:


-3x-6+6=-9+6


-3x=-3

- Then you must divide by -3:


(-3x)/(-3)=(-3)/(-3) \\x=1

Then the answer is:
-3x-6=-9

User Pranav Arora
by
5.6k points